(untitled) (International Journal of Advanced Research in Computer Science, 2017)
The government of India aims at â€œSwachh Bharat Missionâ€ and for that we need smart city with smart streets enabled with smart garbage monitoring system. We see garbage bins around us placed at public places overflowing with due to increase in waste and results into unhygienic conditions for people and leads to deadly diseases. Thus to improve this situation, we proposed this project. In our proposed system, there are multiple smart garbage trash bins on a microcontroller board platform (Arduino Board) located throughout any city or the campus or hospital. The Arduino Board is interfaced with GSM modem and ultrasonic sensor. Once the level of threshold is being crossed, then ultrasonic sensors will trigger the GSM module which in turn continuously alert the authorised person by sending SMS reminder after until the dustbin is cleaned. Beside this, we will also create the central system that will keep showing us the current status of garbage on mobile web browser with html page by wi-fi. With the help of this, we will create shortest path for garbage collection vehicles using Dijkstra Algorithm. This is real time waste management by using smart trash bins that can be accessed anytime anywhere by the concerned person. Keywords: IoT; Smart city; Smart Garbage Bins; Arduino; Ultrasonic Sensors; GSM; Real time Analytics; Route Optimization